Meningitis por Listeria monocytogenes en niñas inmunocompetentes: queso no pasteurizado como probable causa de infección - Valdivia Tapia, María del C. (2015)
Listeria meningoencephalitis is a rare condition, occurring mainly in immunocompromised patients. We present two cases of Listeria monocytogenes meningoencephalitis in immunocompetent children, with successful treatment with betalactam/aminoglycoside combination. Unpasteurized cheese was postulated as the source of infection.